2023
DOI: 10.1002/jeab.868
|View full text |Cite
|
Sign up to set email alerts
|

Effects of economic context and reward amount on delay and probability discounting

Abstract: Steep delay and shallow probability discounting are associated with myriad problem behaviors; thus, it is important to understand factors that influence the degree of discounting. The present study evaluated the effects of economic context and reward amount on delay and probability discounting. Two hundred thirteen undergraduate psychology students completed four delay‐ or probability‐discounting tasks. Participants were exposed to hypothetical narratives involving four bank amounts ($750, $12,000, $125,000, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…Framing change in delay discounting as an adaptation to an evolving environment can also be linked to the literature exploring how the economic context shapes one's tendency to discount future rewards. Studies have shown that individuals living in a context of economic scarcity tend to prefer immediate over delayed rewards more often than people living in wealthier conditions (Anderson et al, 2023;Griskevicius et al, 2011;Mani et al, 2013). One explanation is that preferring an immediateyet smallerreward is a good strategy when the future is too difficult to predict (Burk & Averbeck, 2023;Frankenhuis et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Framing change in delay discounting as an adaptation to an evolving environment can also be linked to the literature exploring how the economic context shapes one's tendency to discount future rewards. Studies have shown that individuals living in a context of economic scarcity tend to prefer immediate over delayed rewards more often than people living in wealthier conditions (Anderson et al, 2023;Griskevicius et al, 2011;Mani et al, 2013). One explanation is that preferring an immediateyet smallerreward is a good strategy when the future is too difficult to predict (Burk & Averbeck, 2023;Frankenhuis et al, 2016).…”
Section: Discussionmentioning
confidence: 99%